Verbal art : a philosophy of literature and literary experience - Pettersson, Anders, 1946- (McGill-Queen's University Press, 2000)
Pettersson demonstrates the implications and applications of the theory through a series of detailed studies of literary works, taking care to show that his theory is compatible with a broad variety of perspectives. Combining an intimate knowledge of modern literary theory and the aesthetics of literature with innovative applications of linguistics and cognitive psychology to the literary work, he provides a thorough treatment of fundamental problems in the area, including the concept of a text or work, the concept of form, and the distinctiveness of the literary use of language.